Β-Blockers for the prevention of acute exacerbations of chronic obstructive pulmonary disease (βLOCK COPD): a randomised controlled study protocol. Issue 6 (7th June 2016) - Bhatt, Surya P; Connett, John E; Voelker, Helen; Lindberg, Sarah M; Westfall, Elizabeth; Wells, J Michael; Lazarus, Stephen C; Criner, Gerard J; Dransfield, Mark T
Abstract : Introduction: A substantial majority of chronic obstructive pulmonary disease (COPD)-related morbidity, mortality and healthcare costs are due to acute exacerbations, but existing medications have only a modest effect on reducing their frequency, even when used in combination. Observational studies suggest β-blockers may reduce the risk of COPD exacerbations; thus, we will conduct a randomised, placebo-controlled trial to definitively assess the impact of metoprolol succinate on the rate of COPD exacerbations. Methods and analyses: This is a multicentre, placebo-controlled, double-blind, prospective randomised trial that will enrol 1028 patients with at least moderately severe COPD over a 3-year period. Participants with at least moderate COPD will be randomised in a 1:1 fashion to receive metoprolol or placebo; the cohort will be enriched for patients at high risk for exacerbations. Patients will be screened and then randomised over a 2-week period and will then undergo a dose titration period for the following 6 weeks. Thereafter, patients will be followed for 42 additional weeks on their target dose of metoprolol or placebo followed by a 4-week washout period. The primary end point is time to first occurrence of an acute exacerbation during the treatment period. Secondary end points include rates and severity of COPD exacerbations; rate of major cardiovascular events; all-cause mortality; lung function (forced expiratory volume in 1 s (FEV1 )); dyspnoea; quality of life; exercise capacity; markers of cardiac stretch (pro-NT brain natriuretic peptide) and systemic inflammation (high-sensitivity C reactive protein and fibrinogen). Analyses will be performed on an intent-to-treat basis. Ethics and dissemination: The study protocol has been approved by the Department of Defense Human Protection Research Office and will be approved by the institutional review board of all participating centres. Study findings will be disseminated through presentations at national and international conferences and publications in peer-reviewed journals. Trial registration number: NCT02587351; Pre-results.